Notes on Early Land Plants Today. 46. Transfer of Vitalianthus urubuensis (Marchantiophyta, Lejeuneaceae) to Cheilolejeunea - Wei, Yu-Mei; He, Qiong; Gradstein, S. Robbert; Campos, Laura V.; Zhu, Rui-Liang (Phytotaxa, 2013)
Vitalianthus was established by Schuster & Giancotti (1993) based on Drepanolejeunea bischleriana K.C.Pôrto & Grolle (1987: 301), which is endemic to the Atlantic coast of north-eastern Brazil. This genus is related to Drepanolejeunea (Spruce 1884: 76) Schiffner (1893: 119) (Gradstein et al. 2001, Gradstein & Costa 2003, He et al. 2012a, b) and characterized by the 1) hyaline papilla at the proximal side of lobule tooth, 2) unbroken basal vitta of 3-7 ocelli in leaf lobes, 3) bilobed underleaves with upright lobes, 4) gynoecial innovations with a pycnolejeuneoid leaf sequence, 5) perianth keels unarmed, and 6) absence of specialized cladia (He et al. 2012a). In addition to the type species, this genus currently also contains Vitalianthus urubuensis Zartman & Ackerman (2002: 267) from the Amazonian rainforests of Brazil and Colombia (Zartman & Ackerman 2002, Mota de Oliveira & ter Steege 2013, Campos et al. in prep.), and V. guangxianus Zhu et al. (2012a: 32). Our examination of type material and recent collections of Vitalianthus urubuensis from Brazil and Colombia reveals that the hyaline papilla of the leaf lobule is distal as in Cheilolejeunea (Spruce 1884: 79) Schiffner (1893: 118) (Fig. 1E,F). The moniliate, unbroken vitta of ocelli in the leaf lobes, one of the most important features of Vitalianthus, also occurs in some species of Cheilolejeunea, e.g. in Cheilolejeunea falsinervis (Sande Lacoste 1854: 321) Schuster & Kachroo (1961: 56) from Asia and Australasia. It thus appears that V. urubuensis is morphologically more similar to Cheilolejeunea than to Vitalianthus. The morphological affinity between Vitalianthus urubuensis and Cheilolejeunea is confirmed by our unpublished molecular data (ITS, trnG and trnL-F; Wei et al., in prep.) which show that V. urubuensis and several species of Cheilolejeunea form a monophyletic lineage. Therefore, the following new combination is necessary.